Roughness comparison of heat cured type of acrylic resin in disinfectant solution immersion (immersion in a solution of alkaline peroxide and 75% celery extract (apium graveolens L)) - Dewi Puspitasari; Diana Wibowo; Elda Rosemarwa (Journal of Dentomaxillofacial Science, 2016)
Acrylic resin denture base has the properties absorbing that affecting physical and mechanical properties. One of the physical properties of acrylic resin is surface roughness. The aim of the study was to find out the roughness effect on heat cured acrylic that was immersed in alkaline peroxide and 75% celery (Apium graveoens L) extract as a disinfectant solution. The study was a true experimental and posttest with control group designed with a rectangular shape size 65 x 10 x 3.3 mm based on the ISO standard 1567, six samples were used for alkaline peroxide, celery extract 75% and aquadest group for 5 and 15 days. A Surface Roughness Tester was used for the surface roughness changes observation. The statistical test used One-way ANOVA and post hoc Bonferroni. The results of this study showed the value of roughness on 5 days for alkaline peroxide (1.51 µm) is greater than celery extract (0.36µm) and aquadest (0.30 µm). The soaking for 15 days in alkaline peroxide (1.52 µm) is greater than 75% celery extracts (0.38 µm) and aquadest (0.34 µm). Alkaline peroxide caused higher roughness value of heat cured acrylic resin than 75% celery extract.